Sistem Informasi Aktivitas Siswa Dalam Kegiatan Ekstrakurikuler Menggunakan Fitur Whatsapp Web: Sistem Informasi Aktivitas Siswa Dalam Kegiatan Ekstrakurikuler Menggunakan Fitur Whatsapp Web - Andi Nur Rachman; Acep Irham Gufroni; Heni Sulastri; Euis Nur Fitriani Dewi (Journal of Appropriate Technology for Community Services, 2024)
Extracurricular activities in the world of education are a necessity for students to improve students' psychomotor skills. Academic activities in participating in extracurricular activities will help students form creative learning patterns and be able to increase creativity in sports and skills in areas of interest and talent. The problem that occurs at Dimitra is that there is no structure in conveying information and monitoring students when taking part in extracurricular activities at Madrasah Tsanawiyah and Madrasah Aliyah Manarul Huda. The information system implemented in this service is expected to help provide information on student development in extracurricular activities and can be monitored by parents. The method applied in this activity uses the Rapid Application Development (RAD) method and applies WhatsApp technology with the aim of much faster development with better quality. From the results of the alpha testing, it shows that the application can be applied to partners for community service within the Madrasah Tsanawiyah and Madrasah Aliyah Manarul Huda as a medium for information on extracurricular developments.